Timor-Leste's Bill of Rights: A Preliminary History - Devereux, Annemarie (ANU Press, 2015)
The Constitution of the Democratic Republic of Timor-Leste of 2002 contains over 40 human rights provisions in its Bill of Rights. In addition to providing an overview of the process leading up to the adoption of the Constitution, this book brings together information relating to each section of the Bill of Rights, presenting: progressive texts produced during the process of the Constituent Assembly; highlights of the arguments put forward within the Constituent Assembly concerning the draft provisions, including alternative proposals advanced; submissions made by Timorese officials, civil society and international bodies; and the results of consultation with the broader community before and during the constitutional process. It is designed to be useful in particular to judges and legal practitioners called upon to interpret the Constitution, government officials and civil society actors involved in human rights work, as well as students of history and constitutional law in Timor-Leste and internationally.